2014
DOI: 10.1249/mss.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Does Not Mediate Resistance Training–Induced Alterations in Resting Metabolic Rate

Abstract: Preventive resistance training elicits an increase in RMR. However, in contrast to currently discussed hypotheses, this increase does not seem to be mediated by training-induced changes in FFM or circulating irisin concentration, which casts doubt in the meaning of irisin for human energy balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
3
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 34 publications
4
69
3
1
Order By: Relevance
“…Although in vitro and in vivo thermogenic effects of irisin have been observed in animal studies [54,76,109,110], the physiological significance in humans remains uncertain. In particular, irisin's potential role in human energy metabolism remains controversial since inconsistent results have been published regarding the exercise-dependent regulation of circulating irisin and its association with energy expenditure [111][112][113][114][115][116][117].…”
Section: Secreted Proteins and Browningmentioning
confidence: 99%
“…Although in vitro and in vivo thermogenic effects of irisin have been observed in animal studies [54,76,109,110], the physiological significance in humans remains uncertain. In particular, irisin's potential role in human energy metabolism remains controversial since inconsistent results have been published regarding the exercise-dependent regulation of circulating irisin and its association with energy expenditure [111][112][113][114][115][116][117].…”
Section: Secreted Proteins and Browningmentioning
confidence: 99%
“…The increase in irisin augments oxygen consumption, improves glucose tolerance and insulin sensitivity, and facilitates weight loss compared with those in an untreated group [1]. Controversies exist among recent publications regarding the importance of irisin and/or fibronectin type III domain containing 5 (FNDC5) in humans [3][4][5][6][7][8][9], and it is necessary to further examine the roles of irisin in metabolic regulation, body composition, and anti-obesity effect.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Pekkala et al [4] reported that irisin concentrations did not change following acute endurance exercise in middle-aged men. The irisin response to resistance training has also been studied [6,7], however, information about the effect of a single bout of resistance exercise on the irisin response is rather limited. Pekkala et al [4] showed that resistance exercise increased FNDC5 mRNA expression approximately 1.4-fold in muscle compared with the baseline value,…”
Section: Introductionmentioning
confidence: 99%
“…Five RCTs 44, 4952 , and all the included CTs and CSS, as well as 22 of the 23 SGS, displayed a high risk of bias due to inadequate generation of a randomised sequence, while four RCTs 23, 33, 42, 53 showed low risk of bias, and three RCTs 41, 54, 55 , as well as one SGS 56 , showed unclear risk of bias because there was no description of the method used for allocation (even though the participants were said to be “randomly” assigned). Six RCTs 23, 42, 49, 50, 52, 53 displayed low risk of bias for “allocation concealment”, while two 44, 54 showed unclear risk of bias because of the lack of description of the randomization allocation. Also, four RCTs 33, 41, 51, 55 , and all the included CTs and SGS, as well as CSS, showed high risk of bias due to the lack of concealment of allocations before assignment.…”
Section: Resultsmentioning
confidence: 99%